Implementation of Community Mental Health Service in Malang, East Java - Zuhrotun Ulya; Adi Sulistyono; Widodo T. Novianto (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: The culture of mental-health care in Indonesia relies heavily on backward pseudo-science rooted in dated spiritual traditions. In Indonesia, some people with mental disorder was shackled in sheds or backyards for years on end, which is known as pasung. Based on report, 1 in 7 mental disorder patients were at risk of pasung. The success of mental health service program need a collaboration from community as preventive and promotive besides curative component. This study aimed to analyze the legal system working based on legal, substance, and law